KEBIJAKAN PENDIDIKAN NASIONAL DAN TANTANGAN PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR DALAM PERSPEKTIF HITORIS: Studi Literatur - Mufidatur Rizqiya Permana; Erma Fatmawati; Imron Fauzi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Education is a strategic instrument in shaping civilization and national progress. Throughout its history, national education policy in Indonesia has undergone continuous changes that reflect the social, political, and cultural dynamics of each administration. These changes have direct implications for the direction and quality of learning, especially in elementary schools as the foundation of national education. This study aims to analyze the development of Indonesia's national education policy from a historical perspective and identify challenges in improving the quality of basic learning. The study uses a qualitative approach with a historical-descriptive literature study method, through an analysis of policies, official documents, and previous research results. The results show that each period has different policy characteristics: the colonial period emphasized discriminatory education, the Old Order emphasized national identity, the New Order was oriented towards stability and equity, while the Reformation to Merdeka Belajar (Freedom of Learning) emphasized decentralization and competency-based quality improvement. However, these policies still face challenges such as quality gaps, limited teacher resources, and infrastructure. In conclusion, changes in national education policy show a continuous direction towards improving the quality of basic learning, although its implementation is not yet evenly distributed across all regions.